KEBIJAKAN DALAM MEMPERTAHANKAN KEBERLANGSUNGAN USAHA UMKM DIMASA PANDEMI COVID-19: KEBIJAKAN DALAM MEMPERTAHANKAN KEBERLANGSUNGAN USAHA UMKM DIMASA PANDEMI COVID-19 - Suwardi; Boediningsih, Widyawati (Faculty of Law, University of Dr. Soetomo, 2021)
The potential market keep business msmb is a national economy due to stand up to economic shocks pademi would emerge problems how to keep to medium enterprise to proceed as any situation thus become immune to any disturbance. How the government efforts in taking so umkm business policy is able to persevere even capable of developing pandemic in a difficult situation. Research methodology used normative, writer research and studies in the norm is legislation or act norm set act no.20 year what policy 2088 about small businesses. A conclusion due to existing covid-19 pandemic since last year 2019 made every effort in crisis. Msmb sector has a very drastic decline in earnings, various obstacles marketing and sales, and distribution of a product with a policy that supported businesses will give the wind players were fresh for him. Traders seek to find an alternative marketing and sales, secure capital and assets owned. Keywords : business policy and sustainability of the pandemic 19